2002
DOI: 10.1063/1.1512815
|View full text |Cite
|
Sign up to set email alerts
|

Electrical measurements of a dithiolated electronic molecule via conducting atomic force microscopy

Abstract: Articles you may be interested inHigh integrity metal/organic device interfaces via low temperature buffer layer assisted metal atom nucleation Nanowell device for the electrical characterization of metal-molecule-metal junctions Measurement of interface potential change and space charge region across metal/organic/metal structures using Kelvin probe force microscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
149
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(156 citation statements)
references
References 13 publications
5
149
0
2
Order By: Relevance
“…Efforts to interpret and use several types of remarkable phenomena that have been observed in organic and molecular-scale devices-phenomena such as molecular rectification (Ranganathan et al 2001;Chabinyc 2002;Vilan et al 2003) and negative differential resistance (Esaki 1958;Gunn 1963;Sollner et al 1983;Rawlett et al 2002;Chen & Reed 2002;Kratochvilova et al 2002b)-have been hampered by the inability of researchers to duplicate each other's results or even construct identical devices and junctions on which to obtain these results. Differing degrees of both intramolecular disorder within the organic film and defects at the metal-organic interfaces (caused by defects in or impurities on the electrodes or the use of different methods of film deposition) are two major sources of irreproducibility of electrical measurements.…”
Section: Reproducibility Of Measurements Of Charge Transportmentioning
confidence: 99%
“…Efforts to interpret and use several types of remarkable phenomena that have been observed in organic and molecular-scale devices-phenomena such as molecular rectification (Ranganathan et al 2001;Chabinyc 2002;Vilan et al 2003) and negative differential resistance (Esaki 1958;Gunn 1963;Sollner et al 1983;Rawlett et al 2002;Chen & Reed 2002;Kratochvilova et al 2002b)-have been hampered by the inability of researchers to duplicate each other's results or even construct identical devices and junctions on which to obtain these results. Differing degrees of both intramolecular disorder within the organic film and defects at the metal-organic interfaces (caused by defects in or impurities on the electrodes or the use of different methods of film deposition) are two major sources of irreproducibility of electrical measurements.…”
Section: Reproducibility Of Measurements Of Charge Transportmentioning
confidence: 99%
“…Regarding the comparison between theory and experiment, however, large discrepancies have been found for some conjugated molecules between theoretical predictions 13,14,15,16,17 and experimental conductances. 1,2,3,4,5,6 Many efforts have been made on the theoretical side 18,19,20,21,22,23 to understand this discrepancy and several possible reasons have been discussed. For example, the self-interaction error (SIE) and the underestimation of the transport gap in density functional theory (DFT) based ab initio calculations, 21,24 and the neglect of the dynamical correlation effect in the non-interacting Landauer formalism.…”
Section: Introductionmentioning
confidence: 99%
“…Electron transport through single conjugated organic molecules has attracted considerable experimental attention 1,2,3,4,5,6,7,8,9,10,11,12 because of the convenience of the chemical assembly and their delocalized electronic states and the resulting small HOMO-LUMO gap which is very useful in molecular electronics especially for the operation under low bias voltages. Theoretically, to understand the transport properties of junctions bridged by these molecules and to be able to calculate their conductance are important in view of both applications and fundamental physics.…”
Section: Introductionmentioning
confidence: 99%
“…It was, however, shown that estimation of the electrical conductance of adsorbed molecules by use of STM is quite complicated compared with techniques in which the electrode is directly attached to the molecules [267][268][269][270][271]. C-AFM has been found to be a good candidate for direct measurement of electrical conduction by organic monolayers such as SAMs [25,[277][278][279][280][281][282][283][284][285][286][287][288]. The advantages of C-AFM over STM are that the electronic properties of a molecular function are sensitive to the effects of deformation caused by the force of interaction between the tip and the sample [25,285,287].…”
Section: Self Assembled Monolayersmentioning
confidence: 99%